2018
DOI: 10.20546/ijcmas.2018.711.029
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rooting Media and IBA Treatments on Shoot Production and Survival of Terminal Cuttings in Guava (Psidium guajava L.) cv. Taiwan Pink

Abstract: The genus Psidium contains 150 species, most of which are fruit bearing trees. The basic chromosomal number of guava is 11. Most of the cultivars are diploid (2n=22), but some are natural and artificial triploids (2n=33), these are generally produce seedless fruits (Jaiswal and Nasim, 1992). In India, guava position in production is fifth after Banana, Mango, Citrus and Papaya (NHB, 2015). It has attained a respectable place and popularity amongst the dietary list of common people in our country owing to nutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
2
2
1
Order By: Relevance
“…An improvement in chlorophyll a and b content was due to NAA 4000 ppm and NAA 2000 ppm over IBA 2000 ppm treatment occurred to the tune of 12.05, 10.23% and 18.52, 13.19% and 10.84, 9.09% and 17.28, 10.99% respectively during corresponding years of study. These findings are contrary with reports of Deb et al (2009) [7] in lemon, Dhatrikarani (2019) [9] and Rani et al (2018) [16] in guava and in agreement with reports of Kachave and Bhosale (2009) [10] in kagzi lime. Rooting media moss grass being significantly effective increased chlorophyll a and b (0.99, 1.03 g/m 2 and 0.98, 1.09 g/m 2 ) to the maximum followed by F. -1).…”
Section: Resultscontrasting
confidence: 95%
“…An improvement in chlorophyll a and b content was due to NAA 4000 ppm and NAA 2000 ppm over IBA 2000 ppm treatment occurred to the tune of 12.05, 10.23% and 18.52, 13.19% and 10.84, 9.09% and 17.28, 10.99% respectively during corresponding years of study. These findings are contrary with reports of Deb et al (2009) [7] in lemon, Dhatrikarani (2019) [9] and Rani et al (2018) [16] in guava and in agreement with reports of Kachave and Bhosale (2009) [10] in kagzi lime. Rooting media moss grass being significantly effective increased chlorophyll a and b (0.99, 1.03 g/m 2 and 0.98, 1.09 g/m 2 ) to the maximum followed by F. -1).…”
Section: Resultscontrasting
confidence: 95%
“…'Thimma', and Rajashekara [15] in stevia cuttings. Similar findings were reported by Rani et al [16] in guava.…”
Section: Number Of Roots Per Cuttingsupporting
confidence: 92%
“…The better response on number of leaves might be due to the better treatment variation and positive response of treatment T 21 . Same findings are Rani et al, (2018) More number of new sprouts per plant and leaves per new sprout were found by the application of IBA at 10,000 ppm with dark colour polythene wrappers and significantly superior to other treatment combinations. It may be due to modification in physiological processes of plants and formation of more number of roots, resulting in the increase in length of the sprouts.…”
Section: Resultssupporting
confidence: 61%
“…The better response on number of leaves might be due to the better treatment variation and positive response of treatment T 21 . Same findings are Rani et al, (2018).…”
Section: Resultsmentioning
confidence: 63%